Prevalence and Burden of Primary Headache Disorders in Kuwaiti Children and Adolescents: A Community Based Study - Al-Hashel, Jasem Yousef; Ahmed, Samar Farouk; Alroughani, Raed (Frontiers in Neurology, 2019)
Background/Objective: Primary headaches are common in the pediatric and adolescent population and it can be disabling for them and their families. We aimed to assess the Prevalence and burden of primary headache disorders among children and adolescents in Kuwait. Methods: A cross-sectional community-based study included Kuwaiti population aged 6-17 years. They were randomly recruited from all six governments of Kuwait using stratified multistage cluster sampling. The Headache-Attributed Restriction, Disability, and Social Handicap and Impaired Participation (HARDSHIP) questionnaire for children and adolescents was used to collect the data. Results: Data were collected from 3423 subjects; 664 subjects were diagnosed as primary headache disorders. The mean age was 12.61 + 2.51 years and 64.2% were females. One-year prevalence of headache was 19.4%. It was significantly prevalent in females compared to males (25.2% versus 13.8%; P <0.001). Primary headache disorder significantly increased in age group 12-17 when compared to age group 6-11 years (25.8% versus 10.4 %; P<0.001). The 1-year prevalence of primary headache showed non-significant difference in both males and female in age group 6-11 years (10.1% in males versus 10.6% in females; P<0.79). While it was significantly higher in female (38.1%) versus males (15.8%); P <0.001 in the age group 12-17 years. Migraine was the most prevalent 10.9%, followed by tension type headache TTH 6.2% and of chronic headache 0.9%. Medical care utilization was reported in 67% of our cohort. The majority (95%) of the patients used symptomatic drugs for headache attacks, whereas only 7.5% % used preventive medication. The students with headache lost mean of 1.29 +1.23 day of school, reported mean 1.16 +1.50 day they could not do activities they had wanted to. Their parents lost mean1.01+1.02 days of work because headache of their children during the preceding 4 weeks of the study. Conclusions: Primary headache prevalence increased with age in adolescents compared to children. There was no gender difference in children; however, it was significantly higher in female adolescents. It can affect schoolwork, social activity and parents` works. The awareness for early diagnosis and preventive medications for headache in this age group may reduce the headache burden.